Titer Antibodi Sebelum dan Sesudah Vaksinasi Hog Cholera pada Babi di Desa Noelbaki Kecamatan Kupang Tengah Kabupaten Kupang - Aloysius Heryanto Wunda; Maxs U.E Sanam; Yohanes TRMR Simarmata (Jurnal Veteriner Nusantara, 2023)
Classical Swine Fever or Hog cholera is an infectious disease in pigs caused by a virus from the family Flaviviridae and genus Pestivirus. One effective way to prevent the spread of Hog cholera is vaccination. This study aims to determine the formation of antibody titers before and after Hog cholera vaccination in pigs in Noelbaki Village, Central Kupang District, Kupang Regency. The samples used for testing were serum samples from 20 pigs aged 2-5 months. Samples were taken twice, namely before and after vaccination. Then the samples were examined at the UPT Veterinary Laboratory of Kupang. The results showed that before vaccinating the serum samples examined, 20 samples did not reach the protective number (PI <40%) and were at -1.69% to 38.67% with an average of 13.95%. In the examination of the sample after vaccination, there were 3 samples that reached the protective number (PI 40%) and 17 samples did not reach the protective number (PI <40%) and were in the range of 4.49% to 46.06% with an average of 26,41%. Then the two research results were tested by paired T-test using the SPSS 16 application. Based on the results of data analysis on the SPSS 16 application, it was stated that there was a relationship between the two groups because the p value <0.05 with a p value of 0.003. The formation of Hog cholera antibody titers in pigs before and after vaccination showed a significant difference between the two groups tested where the p value <0.05.